Child-Pugh Parameters and Platelet Count as an Alternative to ICG Test for Assessing Liver Function for Major Hepatectomy. (29th August 2017) - Au, Kin-Pan; Chan, See-Ching; Chok, Kenneth Siu-Ho; Chan, Albert Chi-Yan; Cheung, Tan-To; Ng, Kelvin Kwok-Chai; Lo, Chung-Mau
Abstract : Objective . To study the correlations and discrepancies between Child-Pugh system and indocyanine green (ICG) clearance test in assessing liver function reserve and explore the possibility of combining two systems to gain an overall liver function assessment. Design . Retrospective analysis of 2832 hepatocellular carcinoma (HCC) patients graded as Child-Pugh A and Child-Pugh B with ICG clearance test being performed was conducted. Results . ICG retention rate at 15 minutes (ICG15) correlates with Child-Pugh score, however, with a large variance. Platelet count improves the correlation between Child-Pugh score and ICG15. ICG15 can be estimated using the following regression formula: estimated ICG15 (eICG15) = 45.1 + 0.435 × bilirubin − 0.917 × albumin + 0.491 × prothrombin time − 0.0283 × platelet (R 2 = 0.455 ). Patients with eICG15 >20.0% who underwent major hepatectomy had a tendency towards more posthepatectomy liver failure (4.1% versus 8.0%, p = 0.09 ) and higher in-hospital mortality (3.7% versus 8.0%, p = 0.052 ). They also had shorter median overall survival (5.10 ± 0.553 versus3.01 ± 0.878 years, p = 0.015 ) and disease-free survival (1.37 ± 0.215 versus0.707 ± 0.183 years, p = 0.018 ). Conclusion . eICG15 can be predicted from Child-Pugh parameters and platelet count. eICG15 correlates with in-hospital mortality after major hepatectomy and predicts long-term survival.